2020
DOI: 10.1186/s12888-020-02510-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relationships among French adult siblings with or without schizophrenia using the ASRQ-S: mediating effect on emotional distress

Abstract: Background: Good sibling relationships in adulthood are known to be a protective factor for mental health. The present study examined and compared the relationships of siblings with either a healthy brother or sister or one experiencing schizophrenia. Methods: In the first phase, we ran a statistical comparison of the two sibling groups on the quality of their sibling relationships (warmth, conflict, and rivalry), emotional distress, and self-esteem. In the second phase, we looked at whether the quality of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(90 reference statements)
0
3
0
1
Order By: Relevance
“…Nevertheless, the addition of SZ-related variables to the regression models only influenced participants' experience of conflict-the dominant dimension in these particular sibling relationships (61). More specifically, our results showed that frequency of treatment and, above all, symptom severity were the best predictors of conflict in SZ sibling group.…”
Section: Addition Of Sz-related Variablesmentioning
confidence: 59%
“…Nevertheless, the addition of SZ-related variables to the regression models only influenced participants' experience of conflict-the dominant dimension in these particular sibling relationships (61). More specifically, our results showed that frequency of treatment and, above all, symptom severity were the best predictors of conflict in SZ sibling group.…”
Section: Addition Of Sz-related Variablesmentioning
confidence: 59%
“…In one of the studies 43.3% of the siblings reported having previous psychological problems compared to the healthy control individuals where none reported having had any psychological problems (Pierazzuoli et al, 2020). Siblings also reported experiencing more emotional distress (effect size d = 0.18) (Plessis et al, 2020), and a higher rate of family history of psychiatric disorder (89.7% versus 10.3%) (Pierazzuoli et al, 2020).…”
Section: More Mental Health Problems and Lower Level Of Well-being Co...mentioning
confidence: 94%
“…Overall, the quality of the sibling relationship was found to be poorer for the sibling group than for the healthy control individuals (effect size d = 1.16 for objective burden and d = 1.81 for subjective burden) in Barak and Solomon (2005). The effect sized ranged from d = 0.15 to d = 0.44 for warmth, conflict and rivalry) in Plessis et al, (2020). The quality of the relationship reported by the sibling declined after the debut of the severe mental illness, whereas during the same period the sibling relationship improved for the normal comparison group.…”
Section: More Mental Health Problems and Lower Level Of Well-being Co...mentioning
confidence: 98%
“…Низка досліджень показує роль стосунків між сиблінгами під час хвороби або інвалідності одного з них. У цих роботах виявлені як позитивні чинники підтримки з боку сестри/брата для хворого, так і погіршення стосунків між ними та страждання, які відчуває здоровий сиблінг внаслідок захворюванні іншого (Bowman et al, 2014;Plessis et al, 2020;Silvén Hagström & Toft, 2019;Tabler et al, 2018).…”
unclassified